Case report: A case of acquired von Willebrand syndrome as onset clinical presentation of systemic lupus erythematosus manifested as epistaxis and pulmonary hemorrhage - Wang, Songmi; Hu, Qun; Chen, Yaxian; Hu, Xiufen; Tang, Ning; Zhang, Ai; Liu, Aiguo (Frontiers in Pediatrics, 2022)
Background Acquired von Willebrand syndrome (AVWS) is a less common bleeding disorder, primarily manifested as mild to moderate mucocutaneous bleeding and laboratory tests are similar to hereditary von Willebrand disease (VWD). AVWS is secondary to other diseases, and systemic lupus erythematosus (SLE) is a relatively rare cause. Case presentation We report a case of AVWS as onset clinical presentation of SLE manifested as epistaxis and pulmonary hemorrhage. A 13-year-old male child presented to the hospital with a six-month history of recurrent epistaxis and a one-month history of anemia. Routine blood tests demonstrated severe normocytic anemia and normal platelet count. Von Willebrand test revealed a significantly lower level. High-resolution chest computed tomography (CT) showed patchy ground glass opacities consistent with hemorrhagic changes. After ruling out the family history, the patient was diagnosed with AVWS. Additional tests confirmed positive antinuclear and anti-Sm antibodies. The underlying SLE was diagnosed and treated with methylprednisolone with disease recovery. Conclusion We recommend screening for bleeding disorders in patients with recurrent epistaxis. AVWS should be considered when laboratory findings suggest hereditary von Willebrand disease without a personal or familial history of bleeding. In addition, the underlying disease should be explored.